Development of the I Take Care of Myself educational game application to enhance early childhood sex education knowledge - Ulfa Khaira; Indryani Indryani; Akhmad Fikri Rosyadi (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2023)
Sexual crimes against children continue to be rampant, and this is due to the fact that children lack the sexual understanding and vocabulary necessary to tell what has happened to them to adults. This study aims to investigate the effectiveness of the android-based educational game application I take Care of Myself on the sexual education of young children. Research and Development (R&D) development research is the methodology employed. This development research technique pertains to the 4-D model (define, design, develop and distribute) (define, design, develop and disseminate). Four experts (material experts, media experts, linguists, and teachers) tested the feasibility of this educational game as a learning medium. Test the hypothesis using the Paired Sample T-test to assess the effectiveness of this educational game. Following the findings of four experts, it was determined that the educational game I take Care of Myself belonged in the very practicable category and should be implemented. The results of the two-tailed significance test indicate that the educational game I take Care of Myself can increase early childhood sexual education knowledge.